Os sete princípios para as boas práticas educacionais e o professor reflexivo no ensino de engenharia: contextos, epistemiologias e tendências - Justi, Almir José Wisniewski (2020)
The methodologies and practices currently used by teachers-engineers-bachelors in engineering courses during their classes, face strong influence of methodologies introduced by the historical constitution of their courses. Strongly built based in empiricism and positivism, education in engineering has advanced and consolidated itself. The pedagogical trends related to these models are linked to the traditional methodology and have prevailed over the years, being still used. Worsening the situation, bachelor-teachers, especially engineers, do not have didactic-pedagogical training and tend to repeat actions of their former teachers. Despite of the current historical moment, the era of knowledge and information is being experienced, the methodologies adopted still remain, which compromises the evolution of education, requiring a critical and reflective teaching posture on the practices adopted. In this way and by considering that the teachers-engineers-bachelors do not have didacticpedagogical training in their graduation, it is questioned how much their teaching practices are convergent with the Seven Principles for Good Practices in Higher Education. Thus, in this work, we investigate the degree of convergence between the practices of bachelor-engineers-teachers at the State University of Western Paraná – UNIOESTE, Foz do Iguaçu and the Seven Principles for Good Practices in Higher Education, through the application of a specific inventory, already consolidated and used in other countries. Allied to the application of the inventory, we searched for evidence of reflective positions of the teachers through the relationship established between the characteristics of the reflective teacher and the Seven Principles. Methodologically, the research developed has a quantitative approach, with descriptive objectives and, in relation to the procedures, it is a survey research. The data were analyzed in a quantitative and qualitative way. It was observed that the practices of the researched teachers show weak convergence, in five of the Seven Principles addressed, however, when analyzed individually, the attitudes most valued by the researched teachers coincide with the teaching characteristics related to the adoption of a reflective posture. It is hoped to provide opportunities for this work, reflections and constructive criticisms, updates and adjustments regarding the pedagogical and methodological actions of the bachelor-engineers-teachers, contributing to the rethinking of the practices adopted and, consequently, to the improvement of the teaching and learning process.